Circular solar: Evaluating the profitability of a photovoltaic panel recycling plant. Issue 6 (June 2023) - D'Adamo, Idiano; Ferella, Francesco; Gastaldi, Massimo; Ippolito, Nicolò M; Rosa, Paolo
Photovoltaic (PV) panels have a crucial role in coping with the global warming mitigation and the energetic crisis currently affecting the European Community. However, from the circular perspective of end-of-life (EoL) management, there are still big issues to be solved in order to recover materials from this kind of e-wastes. Because of several reasons (e.g. type of embedded materials, illegal shipments, location of manufacturers) EoL businesses do not have the interest in approaching them. This poses a significant environmental concern in terms of their management. This work wants to assess the profitability of a specific PV module recycling plant, by evaluating several market contexts in which multiple scenarios of material price, investment and process costs will be considered. The results for a 3000 tonnes plant show that profitability is not verified in the absence of an avoided landfill cost. Instead, when a value of 200 €/tonnes is applied, the net present value is positive in 35.2% of the scenarios and at 87.6% when a value of 350 €/tonnes is considered. The policy choice of this value requires linking the PV module disposal fee to the circular benefits associated with its recovery.